SUPPLY NETWORKS AND INNOVATION ACTIVITY IN MEDIUM-HIGH TECHNOLOGY MANUFACTURING INDUSTRIES IN POLAND - Piotr Dzikowski (Acta Scientiarum Polonorum. Oeconomia, 2018)
Increasing market dynamics requires the involvement of an increasing number of partners, including suppliers, customers and competitors located near the company and in its further surroundings. The interaction between participants in such networks leads to the exchange of knowledge and information, and this process takes on unique forms specific to the participants and the environment in which they occur. The study aims to determine the influence of distance and type of relationships with a competitor, supplier, and customer on the type of innovative activity in medium-high technology companies in Poland. The work assumes that close contacts with a competitor, supplier, and customer operating within a short distance support innovative activities. Domestic and foreign suppliers, customers and competitors are favored to undertake innovative activities, and the most positive influence on the stimulation of innovative activity is the cooperation with suppliers and foreign customers.